TEACHERS' PERCEPTIONS OF ARTIFICIAL INTELLIGENCE TOOLS IN ENGLISH LANGUAGE TEACHING: OPPORTUNITIES, CONCERNS, AND PEDAGOGICAL READINESS - Daniel Zulhendra; Muhammad Faisal (SENSEI RESEARCH CENTER, 2023)
Artificial intelligence tools are increasingly influencing English language teaching by supporting lesson planning, materials development, automated feedback, assessment preparation, translation, pronunciation practice, and personalized learning. However, teachers' perceptions remain central because the pedagogical value of artificial intelligence depends not only on technological capability but also on teachers' readiness, ethical awareness, instructional beliefs, and classroom decision-making. This study aims to examine English teachers' perceptions of artificial intelligence tools in English language teaching, focusing on perceived usefulness, pedagogical opportunities, ethical concerns, and professional support needs. The study employed a mixed-method design involving a survey of 86 English teachers and semi-structured interviews with 14 selected teachers. Quantitative data were analyzed using descriptive statistics and correlation analysis, while qualitative data were analyzed thematically. The findings show that teachers generally perceived artificial intelligence tools as useful for preparing teaching materials, generating practice tasks, improving writing feedback, adapting text difficulty, and supporting student engagement. However, teachers also expressed concerns about accuracy, overdependence, academic integrity, data privacy, algorithmic bias, and reduced student originality. The strongest perceived need was professional development on pedagogical integration, ethical use, prompt design, and classroom policy. The study concludes that artificial intelligence tools can support English language teaching when teachers use them critically, selectively, and transparently. Artificial intelligence should not replace teacher judgment but should function as a pedagogical assistant that strengthens instructional design, feedback quality, and learner support.